1998
DOI: 10.1111/j.1469-7793.1998.317be.x
|View full text |Cite
|
Sign up to set email alerts
|

An ether ‐à‐go‐go K+ current, Ih‐eag, contributes to the hyperpolarization of human fusion‐competent myoblasts

Abstract: The skeletal muscle fibre is a postmitotic multinucleated cell formed by the fusion of mononucleated myoblasts. Myoblast fusion is essential to skeletal muscle development and repair, and understanding this process is important for myoblastbased grafts or gene therapies. Our recent work on human fusion-competent myoblasts indicates that an early step in the fusion process is a hyperpolarization of the resting potential. This hyperpolarization is a two-step mechanism involving the sequential expression of two v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 21 publications
6
69
1
Order By: Relevance
“…On the other hand, EAG mRNA is expressed in several cancer cell lines including HeLa, MCF-7, SHSY-5Y, and IGR1 from carcinoma of the cervix, breast tumor, neuroblastoma, and melanoma, respectively (9,10). Despite the major expression of EAG in normal brain (9), endogenous EAG-mediated currents have been reported only in myoblasts (6) and in the tumoral cell lines SHSY-5Y (4), MCF-7 (11), and IGR1 (10). Eag is expressed in the tumor cell line HeLa (9); however, no EAG-mediated currents have been described in these cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, EAG mRNA is expressed in several cancer cell lines including HeLa, MCF-7, SHSY-5Y, and IGR1 from carcinoma of the cervix, breast tumor, neuroblastoma, and melanoma, respectively (9,10). Despite the major expression of EAG in normal brain (9), endogenous EAG-mediated currents have been reported only in myoblasts (6) and in the tumoral cell lines SHSY-5Y (4), MCF-7 (11), and IGR1 (10). Eag is expressed in the tumor cell line HeLa (9); however, no EAG-mediated currents have been described in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid down-regulates hEAG current in neuroblastoma cells (4). hEAG is transiently expressed before myoblasts fusion, which is a cell cyclerelated event (5,6). hEAG current decreases during M phase and is modulated by cytoskeletal elements (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once activated, these cells start to proliferate as myoblasts and then differentiate and fuse into newly formed myotubes or damaged fibers. Electrophysiological studies performed on healthy human myoblasts indicated that the appearance of voltage-gated K + channels and the setting of the resting membrane potential (RMP) in the vicinity of -60 mV are processes associated with cell fusion [21][22][23][24]. Therefore, it has been proposed that cell hyperpolarization, associated with the expression of two K + currents, I K(NI) , a non-inactivating delayed rectifier, and I K(IR) , an inward rectifier, is involved in the mechanism of Ca 2+ influx, an event observed prior to the cell fusion of human myoblasts [23].…”
Section: Introductionmentioning
confidence: 99%
“…No information about its expression in melanocyte has been reported. While its function in the brain remains unknown, Eag1 has been involved in skeletal muscle development, the channel being transiently expressed in the onset of myoblasts fusion (Bijlenga et al, 1998). Remarkably, Eag1 is associated with tumours development in patients and animals.…”
Section: Voltage-gated Potassium Channels and Eag1mentioning
confidence: 99%